3D printing polymer, metal and gel based additive manufacturing - Singh, Rupinder 1979-; Kumar, Ranvijay; Kumar, Vinay; Davim, J. Paulo 1964- (De Gruyter series in advanced mechanical engineering, 2024)
The book provides a detailed methodology for addressing the needs of material processing (polymer/ metals/ bio-gels etc.) and various engineering applications in the next 5-10 years. The book presents a detailed mechanical, morphological, thermal, and rheological characterization of selected materials and highilights the required environmental standards to be maintained.